Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3892/ijo.31.4.915
|View full text |Cite
|
Sign up to set email alerts
|

The plant alkaloid cryptolepine induces p21WAF1/CIP1 and cell cycle arrest in a human osteosarcoma cell line

Abstract: Abstract. We previously established a bioassay method to screen for compounds that activate the promoter activity of p21 WAF1/CIP1 , a potent inhibitor of cyclin-dependent kinases, in a p53-independent manner. As an activator of p21 WAF1/CIP1promoter activity, we isolated cryptolepine (CLP: 5-methyl indolo (2,3b)-quiniine), an indoloquinoline alkaloid, from the traditional Ayurvedic medicinal plant Sida cordifolia. We show here that CLP induces the expression of p21 WAF1/CIP1with growth arrest in p53-mutated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…The p21 gene expression product, p21 protein, is an inhibitor of cyclin cell-cycle dependent kinase. Recent studies have shown that cyclins and their related cyclin-dependent kinases (CDKs) play important roles in the control of the cell cycle [25,26]. Another study investigated the expression of cell-cycle mediators in ovarian cancer cells after transfection with p21 and p53, and found that cell growth was inhibited after transfection [27].…”
Section: Discussionmentioning
confidence: 99%
“…The p21 gene expression product, p21 protein, is an inhibitor of cyclin cell-cycle dependent kinase. Recent studies have shown that cyclins and their related cyclin-dependent kinases (CDKs) play important roles in the control of the cell cycle [25,26]. Another study investigated the expression of cell-cycle mediators in ovarian cancer cells after transfection with p21 and p53, and found that cell growth was inhibited after transfection [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although cryptolepine has not been comprehensively studied with respect to anti-cancer activity, in vitro studies in tumour cell lines have found it to intercalate into DNA, inhibit topoisomerase II, induce p21WAF1/CIP1 and thereby elicit cell cycle arrest and apoptotic cell death [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…315,316 The total synthesis of 336 was achieved as illustrated in Scheme 72. The total synthesis started from coupling of 1,5-naphthalenediol mono-methoxymethyl (MOM) ether 329 with bromobenzoquinone 330 mediated by K 2 CO 3 in DMSO 317 to afford a C-O coupling product.…”
mentioning
confidence: 99%